Adsorption of Some Alkaline Metals and Alkaline Earth Metals on Carbon Nanotube - Vadi, Mehdi; Maleki, Alireza; Poladian, Frank (Asian Journal of Chemistry, 2011)
In this work, the adsorption of some alkaline metals and alkaline earth metal nitrates on carbon nanotube have been measured. The results are significant for biologists, druggists and any one who investigate on alkaline metals and alkaline earth metals on carbon nanotube. This function is most important for Physicians to treat cancer or Osseo emptiness and by that we can loose water hardly and filtration. In this studies the alkaline nitrate and alkaline earth nitrate, mixed with carbon nanotube then after 5 min the amount of the compounds adsorbed on carbon nanotube was measured by atomic adsorption spectrometer method. Alkaline metals have more adsorption in comparison of alkaline earth metals on carbon nanotube.